If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13w+19w-7+2=-4w+2-7
We move all terms to the left:
13w+19w-7+2-(-4w+2-7)=0
We add all the numbers together, and all the variables
13w+19w-(-4w-5)-7+2=0
We add all the numbers together, and all the variables
32w-(-4w-5)-5=0
We get rid of parentheses
32w+4w+5-5=0
We add all the numbers together, and all the variables
36w=0
w=0/36
w=0
| k/5+2=19 | | (5/6)y=-5/9 | | 0.25(3+b)=0.5 | | 10x-2=4x+12 | | -3z=6z-11 | | 23-8x=4 | | 3(x)=2x+1 | | 4x+22+2x+38=180 | | 6+9=-3(6x-5) | | 6x×4=24 | | 1/7y=-12/13 | | 8x-2=8(x-1) | | 4x-12x+3=3x-4 | | 9=14x-4x | | x+(x=2)=126 | | -3z=6z=11 | | 8k-3(2k+4)=3(k-6) | | -17+38=-3(x+1) | | x+3/16=7/8+x-5/9 | | 6(y-1.4)=3.5y+1.6 | | (2w-1)=40 | | 2/3a+29/8=-11/a-3/2 | | w+25=64 | | z/31=27 | | X-20=2x+20 | | 282=v-85 | | 12x-17=5x-3 | | 10-6p=-104 | | p/8=8 | | 2+8m=37+3m | | 113=y3-9 | | 0.7×x=273 |